The influence of acute dietary carbohydrate manipulation on 2000m rowing performance and metabolism - Stephens, S.; Osborne, M.; MacKinnon, L. T.; Jenkins, D. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The benefits of carbohydrate (CHO) loading prior to competitive endurance events have been well established. Few studies, however, have examined the effect of acute dietary manipulation prior to high intensity exercise performance. The purpose of this study was to examine whether dietary manipulation influenced 2000m rowing performance and metabolism. On three separate occasions, twelve sub-elite male rowers performed a maximal 2000m rowing ergometer trial. Three days prior to each performance trial (PT), subjects were randomly assigned to one of three conditions, high CHO (HC), Control (C), or low CHO (LC). For each PT, performance time, oxygen consumption VO2 heart rate (HR) and pre- and post-exercise blood lactate conc entration (B[LA-]), pH,PCO2 and bicarbonate (HCO3-) levels were measured. Total energy derived in the form of CHO was significantly greater in the HC condition (77.1%) than in the C condition (51%), which in turn was significantly higher than the LC condition (33.3%) (p<0.0001). No difference in 2000m performance (p=0.64) was found between the three dietary conditions. Similarly, there was no difference in peak HR (p=0.35), pre-exercise VO2 (p=0.85), exercising VO2 (p=0.24) or maximal accumulated oxygen deficit (MAOD) (p=0.45). Significantly higher pre-exercise RER (p<0.05) and exercising RER values (p<0.01) were evident in the HC condition compared with the C and LC conditions. This finding, combined with the observation that significantly higher pre- and immediately post-exercise B[La-] were apparent in the HC condition compared with the LC (p=0.0025), suggests that glycolysis may increase under resting and exercising conditions following a high CHO diet. Pre-exercise blood pH was also significantly higher in the HC condition than the LC condition (p=0.049). This was independent of any differences in pre-and post-exercise HCO3- and PCO2 between the three conditions. In conclusion, dietary manipulation had no influence on 2000m rowing ergometer performance. Apart from a small decrease in pre-exercise blood pH in the LC condition, possibly due to induced respiratory alkalosis, the increase in glycolysis associated with a high CHO diet did not change the acid-base status of blood. The changes in B[La-], which occurred independently of changes in blood pH, HCO3- and PCO2 suggest there was improved lactate efflux from the muscle and increased removal from the blood.